Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 2:
a: =>3/4x=-3/5-1/2=-11/10
\(\Leftrightarrow x=\dfrac{-11}{10}:\dfrac{3}{4}=\dfrac{-11}{10}\cdot\dfrac{4}{3}=-\dfrac{44}{30}=-\dfrac{22}{15}\)
b: \(\Leftrightarrow x+\dfrac{3}{4}x=\dfrac{1}{3}+\dfrac{5}{4}=\dfrac{19}{12}\)
=>7/4x=19/12
=>x=19/21
c: \(\Leftrightarrow-\dfrac{2}{3}x+\dfrac{1}{6}=\dfrac{2}{3}x-\dfrac{1}{3}\)
=>-4/3x=-1/3-1/6=-1/2
=>x=1/2:4/3=1/2x3/4=3/8
Bài 1
\(\dfrac{1}{7}:\dfrac{5}{17}-\dfrac{3}{2}.\left(\dfrac{1}{6}-\dfrac{7}{12}\right)\)
\(\dfrac{1}{7}.\dfrac{17}{5}-\dfrac{3}{2}.\left(-\dfrac{5}{12}\right)\)
\(\dfrac{17}{35}-\left(-\dfrac{5}{8}\right)\)
\(\dfrac{17}{35}+\dfrac{5}{8}\)
\(\dfrac{311}{280}\)
a) \(3\frac{1}{3}\left(3\frac{1}{4}+2x\right)=6\frac{2}{3}\)
\(3\frac{1}{3}\times3\frac{1}{4}+2x=6\frac{2}{3}\)
\(10\frac{5}{6}+2x=6\frac{2}{3}\)
\(2\times x=6\frac{2}{3}+10\frac{5}{6}=17,5\)
\(x=17,5\div2=8,75\)
Vậy x = 8,75
b) \(x-25\%x=\frac{6}{11}\left(\frac{1}{2}+\frac{3}{4}-\frac{1}{3}\right)\)
\(x-\frac{25}{100}x=\frac{6}{11}\left(\frac{1}{2}+\frac{3}{4}-\frac{1}{3}\right)\)
\(x-\frac{1}{4}\times x=\frac{6}{11}\times1\frac{7}{12}=\frac{19}{22}\)
\(x\times x=\frac{19}{22}+\frac{1}{4}=\frac{49}{44}\)
\(\Rightarrow2x\left(x\times x\right)=\frac{49}{44}\)
\(x=\frac{49}{44}\div2=\frac{49}{88}\)
Vậy x = \(\frac{49}{88}\)
c) \(\left(4,5-2x\right)\times1\frac{4}{7}=\frac{11}{14}\)
\(4,5-2x\times1\frac{4}{7}=\frac{11}{14}\)
\(-2x\times1\frac{4}{7}=\frac{11}{14}-4,5=-3\frac{5}{7}\)
\(-2\times x=-3\frac{5}{7}\div1\frac{4}{7}=-2\frac{4}{11}\)
\(x=-2\frac{4}{11}\div\left(-2\right)=1\frac{2}{11}\)
Vậy x = \(1\frac{2}{11}\)
d) \(-3^2-|2x+3|=4\)
\(9-|2x+3|=4\)
\(-|2x+3|=4-9=-5\)
\(-|2x|=-5-|3|=-8\)
\(-|x|=-8\div2=-4\)
\(-x=4\Rightarrow x=-4\)
Vậy x = -4 (-x được xem là số đối của x)
B= 1/2 x 2/3 x 3/4 x ...........x 2002/2003 x 2003/2004
1 x 2 x 3 x 4 x .............x 2002 x 2003
2 x 3 x 4 x .............x 2003 x 2004
1
2004
b: \(\Leftrightarrow1-\dfrac{1}{12}+\dfrac{1}{12}-\dfrac{1}{23}+\dfrac{1}{23}-\dfrac{1}{34}+...+\dfrac{1}{89}-\dfrac{1}{100}+x=\dfrac{5}{3}\)
=>x+99/100=5/3
=>x=5/3-99/100=203/300
c: \(\Leftrightarrow\left(\dfrac{1}{11}-\dfrac{1}{13}+\dfrac{1}{13}-\dfrac{1}{15}+...+\dfrac{1}{19}-\dfrac{1}{21}\right)-x+4+\dfrac{221}{231}=\dfrac{7}{3}\)
\(\Leftrightarrow\dfrac{10}{231}-x+4+\dfrac{221}{231}=\dfrac{7}{3}\)
=>5-x=7/3
hay x=8/3